Уточнение субсолидусного строения системы ВаО – Аl₂О₃ – Fе₂О₃ - Шабанова, Галина Николаевна; Иващенко, М. Ю.; Ворожбиян, М. И.; Костыркин, О. В.; Киселева, С. А. (НТУ "ХПИ", 2012)
В статье приведены результаты исследования субсолидусного строения трехкомпонентной системы ВаО – Аl₂О₃ – Fе₂О₃, проведена ее триангуляция при температуре 13000 ⁰С и определены геометро-топологические характеристики данной системы. Полученные результаты позволяют прогнозировать фазовый состав барийсодержащих вяжущих материалов с комплексом необходимых физико-механических и технических свойств.

The results of the investigation of subsolidus structure of three-component system ВаО – Аl₂О₃ – Fе₂О₃ has been presented in the article. It is triangulation under the temperature of 13000 ⁰C has been conducted and geometrical-topological characteristics of the given system has been determined. The results obtained let us forecast phase composition of barium-containing binding materials with a complex of the necessary physico-mechanical and technical properties.
Keywords: триангуляция; барийсодержащие вяжущие; прогнозирование; subsolidus structure; triangulation; probability; phase coexistence